Cationic Heterobimetallic Mg(Zn)/Al(Ga) Combinations for Cooperative C-F Bond Cleavage - Friedrich, Alexander; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2021)
Low-valent ((BDI)-B-Me)Al and ((BDI)-B-Me)Ga and highly Lewis acidic cations in [((BDI)-B-tBu)M+.C6H6][(B(C6F5)(4)(-)] (M=Mg or Zn, (BDI)-B-Me=HC[C(Me)N-DIPP](2), (BDI)-B-tBu=HC[C(tBu)N-DIPP](2), DIPP=2,6-diisopropylphenyl) react to heterobimetallic cations [((BDI)-B-tBu)Mg-Al((BDI)-B-Me)(+)], [((BDI)-B-tBu)Mg-Ga((BDI)-B-Me)(+)] and [((BDI)-B-tBu)Zn-Ga((BDI)-B-Me)(+)]. These cations feature long Mg-Al (or Ga) bonds while the Zn-Ga bond is short. The [((BDI)-B-tBu)Zn-Al((BDI)-B-Me)(+)] cation was not formed. Combined AIM and charge calculations suggest that the metal-metal bonds to Zn are considerably more covalent, whereas those to Mg should be described as weak Al-I(or Ga-I)-> Mg2+ donor bonds. Failure to isolate the Zn-Al combination originates from cleavage of the C-F bond in the solvent fluorobenzene to give ((BDI)-B-tBu)ZnPh and ((BDI)-B-Me)AlF+ which is extremely Lewis acidic and was not observed, but ((BDI)-B-Me)Al(F)-(mu-F)-(F)Al((BDI)-B-Me)(+) was verified by X-ray diffraction. DFT calculations show that the remarkably facile C-F bond cleavage follows a dearomatization/rearomatization route.
CRIS-Team WoS Importer:2021-06-25